Effects of artificial depletion of the bile acid pool in man. Issue 7 (July 1986) - Jazrawi, R P; Bridges, C; Joseph, A E; Northfield, T C
Abstract : In order to elucidate the relationship between bile acid pool size and cholesterol saturation index of fasting state gall bladder bile, we artificially depleted the bile acid pool in 12 healthy volunteers. Bile acid pool size decreased from 7.6 +/- 0.9 to 5.8 +/- 0.7 mmol (mean +/- SEM, p less than 0.01), and saturation index of fasting state gall bladder bile increased from 0.93 +/- 0.07 to 1.18 +/- 0.07 (p less than 0.001). There was no alteration in saturation index of basal or stimulated hepatic bile. There was no change in gall bladder storage of basal hepatic bile, nor in the proportion of the bile acid pool stored in the gall bladder. The bile acid mass in the gall bladder fell from 4.9 +/- 0.5 to 3.4 +/- 0.4 mmol (p less than 0.05) and phospholipid mass from 1.6 +/- 0.3 to 1.2 +/- 0.2 mmol (p less than 0.05), but there was no change in cholesterol mass. The gall bladder volume fell from 30 +/- 4 to 18 +/- 2 ml (p less than 0.01). These results suggest that artificial depletion of the bile acid pool increased saturation index of fasting state gall bladder bile without altering saturation index of basal or stimulated hepatic bile; it probably increased the ratio of basal: stimulated hepatic bile within the gall bladder by decreasing gall bladder storage of stimulated hepatic bile.